Interactive Brain Activity: Review and Progress on EEG-Based Hyperscanning in Social Interactions - Liu, Difei; Liu, Shen; Liu, Xiaoming; Zhang, Chong; Li, Aosika; Jin, Chenggong; Chen, Yijun; Wang, Hangwei; Zhang, Xiaochu (Frontiers in Psychology, 2018)
When individuals interact with others, perceived information is transmitted among their brains. The EEG-based hyperscanning technique, which provides an approach to explore dynamic brain activities between two or more interactive individuals and their underlying neural mechanisms, has been applied to study different aspects of social interactions since 2010. Recently there has been an increase in research on EEG-based hyperscanning of social interactions. This paper summarizes the application of EEG-based hyperscanning on the dynamic brain activities during social interactions according to the experimental designs and contents, discusses the possibility of applying inter-brain synchrony to social communication systems and analyzes the contributions and the limitations of these investigations. Furthermore, this paper sheds light on some new challenges to future EEG-based hyperscanning studies and the emerging field of EEG-based hyperscanning for pursuing the broader research field of social interactions.